Implementation of Academic Information System at Al-Inayah Pamulang Quran House, South Tangerang - Mulyana, Dadang Iskandar; Sodik; Zidane, Ahmad Syahran; Hidayat, Riza; Rochman, Fatchur (International Journal Software Engineering and Computer Science (IJSECS), 2024)
In today's digital era, technology profoundly influences various societal domains, notably education. Rumah Quran Al-Inayah Pamulang, a non-formal educational center in Tangerang Selatan, fosters Quran memorization and practice among Muslim children. However, its manual system requires enhancement for better accuracy and timeliness in managing information. A web-based academic information system is proposed, utilizing the waterfall model methodology to address this. This system aims to streamline data collection, monitor memorization progress efficiently, and ensure organized data storage. The Academic Information System of Rumah Quran Al-Inayah Pamulang is a digital platform facilitating student information management, activity scheduling, academic progress tracking, and parent communication.